APPLICATION OF VIBRATION MEASUREMENT TO DETECT DAMAGE IN CASTING (Journal of Engineering, 2006)
Modal testing has become commonplace in many industries today as a research and development tool. In this capacity, it is used primarily during product prototype development and for vibration problem in general. Many types of structural or parts faults will cause changes in the measured dynamic response of a structure. These changes will, in turn, cause change in the structure's modal parameter. The purpose of the present work is to propose an improved damage detection and location based on the measurement of modal parameter (natural frequency and mode shape) before and after faults, which they have varying extents, for three different sizes of Aluminum casing plates. This local damage can be translated into or characterization as a reduction of the local stiffness which, simulated in the presented numerical models using software package. After measured natural frequency, if a change is detected a statistical method is used to make the best match between the measured changes in frequencies and the family of the theoretical predictions. This predicts the most likely defect location. Analytical results are also used to check numerical results, which showed a good agreement with it. Standard Aluminum plates were also investigated in this work. It results were compared with casting results for two boundary conditions. Also, the defect location charts that plotted with the support of deriving stiffness sensitivity equation showed a good agreement between the predicted defect site and the actual defect location for most of the study cases